A computer model of comprehensive modeling of the laser time-of-flight analyzer. Issue 4 (August 2017) - Karpov, Alexander V; Sysoev, Alexander A
This article offers a new approach to computer modeling of time-of-flight analyzers of mass spectrometers. The main feature of the model is comprehensive tracking of the processes from the laser plasma generation until the final stage, on which the isotopic or elemental composition is determined for the analyzed solid sample. Apart from usual models based on SIMION-8 3D or similar software, this article proposes fundamentally new modeling stages. These stages are (1) generation and spread of laser plasma, (2) formation of the ion packages, (3) ion detection, and (4) formation and processing of the analytical signals. In order to provide consistent modeling of all the stages, special software units were developed. Program control of the analyzer ion optics (electrodes voltages) allows scan of mass spectra by ion energy. Additional complex of the programs provides simulation of mass spectra digitization, summation of digitized mass spectra for a wide range of variable parameters, and consideration of the discriminatory effects. According to the data, the software calculates ion-optical characteristics of the analyzer and the analytical parameters of measurement results.